A dynamic capabilities-based entrepreneurial theory of the multinational enterprise - Teece, David J (Journal of International Business Studies, 2014)
This paper develops a dynamic capabilities-based theory of the multinational enterprise (MNE). It first reviews scholarship on the MNE, with a focus on what has come to be known as "internalization" theory. One prong of this theory develops contractual/transaction cost-informed governance perspectives; and another develops technology transfer and capabilities perspectives. In this paper, it is suggested that the latter has been somewhat neglected. However, if fully integrated as part of a more complete approach, it can buttress transaction cost/governance issues and expand the range of phenomena that can be explained. In this more integrated framework, dynamic capabilities coupled with good strategy are seen as necessary to sustain superior enterprise performance, especially in fast-moving global environments. Entrepreneurial management and transformational leadership are incorporated into a capabilities theory of the MNE. The framework is then used to explain how strategy and dynamic capabilities together determine firm-level sustained competitive advantage in global environments. It is suggested that this framework complements contract-based perspectives on the MNE and can help integrate international management and international business perspectives.